What do patients with glaucoma see: a novel iPad app to improve glaucoma patient awareness of visual field loss. Issue 2 (20th November 2020) - Gagrani, Meghal; Ndulue, Jideofor; Anderson, David; Kedar, Sachin; Gulati, Vikas; Shepherd, John; High, Robin; Smith, Lynette; Fowler, Zachary; Khazanchi, Deepak; Nawrot, Mark; Ghate, Deepta
Abstract : Purpose: Glaucoma patients with peripheral vision loss have in the past subjectively described their field loss as 'blurred' or 'no vision compromise'. We developed an iPad app for patients to self-characterise perception within areas of glaucomatous visual field loss. Methods: Twelve glaucoma patients with visual acuity ≥20/40 in each eye, stable and reliable Humphrey Visual Field (HVF) over 2 years were enrolled. An iPad app (held at 33 cm) allowed subjects to modify 'blur' or 'dimness' to match their perception of a 2×2 m wall-mounted poster at 1 m distance. Subjects fixated at the centre of the poster (spanning 45° of field from centre). The output was degree of blur/dim: normal, mild and severe noted on the iPad image at the 54 retinal loci tested by the HVF 24-2 and was compared to threshold sensitivity values at these loci. Monocular (Right eye (OD), left eye (OS)) HVF responses were used to calculate an integrated binocular (OU) visual field index (VFI). All three data sets were analysed separately. Results: 36 HVF and iPad responses from 12 subjects (mean age 71±8.2y) were analysed. The mean VFI was 77% OD, 76% OS, 83% OU. The most common iPad response reported was normal followed by blur. No subject reported dim response. The mean HVF sensitivity threshold was significantly associated with the iPad response at the corresponding retinal loci (For OD, OS and OU, respectively (dB): normal: 23, 25, 27; mild blur: 18, 16, 22; severe blur: 9, 9, 11). On receiver operative characteristic (ROC) curve analysis, the HVF retinal sensitivity cut-off at which subjects reported blur was 23.4 OD, 23 OS and 23.3 OU (dB). Conclusions: Glaucoma subjects self-pictorialised their field defects as blur; never dim or black. Our innovation allows translation of HVF data to quantitatively characterise visual perception in patients with glaucomatous field defects.